Cross-border insolvencies in the European Union: recent case law and new challenges - Torralba Mendiola, Elisa (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Regulation 2015/848 on Insolvency Proceedings rules the private international law matters regarding insolvencies within the European Union. This paper analyses the most recent case law of the EUCJ and the challenges actually existing in this area, that evidence the need to adapt the application of the rules to the changing legal and political context.
Keywords: insolvency; cooperation; jurisdiction